The right choices Bible - McDowell, Dottie; McDowell, Josh.; Boddy, Joe. (Dallas, Texas : Tyndale House Publishers, 2007)
Over sixty stories from the Old and New Testaments, in which the main character must make an important choice.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Bible stories, English